Prevalence, species distribution, and risk factors of fungal colonization and infection in patients at a burn intensive care unit in Vietnam - Bang Nguyen; Nguyen Xuan; Dinh Quang; Cao Loi; Nguyen Minh; Nguyen Lam; Do Anh; Truong Hien; Hoang Su; Tran-Anh Le (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Burn patients are at a higher risk of infections caused by different organisms. This study aimed to address the prevalence, causative species, and factors related to fungal colonization or infection in patients with acute severe injuries admitted to the intensive care unit (ICU) of a burn hospital in northern Vietnam. Materials and Methods: This prospective study was conducted on 400 patients in a burn ICU between 2017 and 2019. Clinical samples were weekly collected and screened for fungi, and relevant clinical information was obtained from medical records. Results: According to the results, 90% of the patients were colonized with fungi. Out of this group, 12.75% of the cases had invasive fungal infection (IFI). Eleven yeasts and six mold species were isolated from the patients, with the most common species being Candida tropicalis (45.56%) and C. albicans (41.94%). Among the eleven species causing fungal wound infection (FWI), the most common agents were Candida (66.7% of FWI patients) and Aspergillus (38.5%) species. Three Candida species isolated from blood were C. tropicalis (66.7%), C. albicans (20.0%), and C. parapsilosis (14.3%). No factors were found to expose the patients to a higher risk of fungal colonization. However, hyperglycemia, prolonged ICU stay, and heavy Candida species colonization were found to be independently predictive of IFI. Conclusion: Burn patients are at the risk of fungal infection with Candida species (especially C. tropicalis) and Aspergillus as the most frequently responsible agents. Continuous surveillance of fungi and appropriate management of pathophysiological consequences are essential to prevent fungal infection in burn patients.